Biometrical Stability and Economic Viability of Aus Rice Genotypes under Direct Seeding in Bangladesh: An Assessment of Yield, Profitability, and Greenhouse Gas Footprint - Habib, Muhammad Ashraful; Nayak, Swati; Islam, S.M. Mofijul; Islam, Saidul; Nuruzzaman; Mohapatra, Subhasmita (International Rice Research Institute, 2025)
This study evaluated the agronomic, economic, and environmental performance of five rice genotypes across two major rice-growing regions of Bangladesh (Rajshahi and Rangpur). The experiment was conducted in direct-seeded rice systems during the Aus seasons 2023 to 2025, using head-to-head adaptive trials (HHAT) through a farmer-participatory approach. Key performance indicators included canopy coverage, harvest duration, equivalent yield, economic benefit, benefit-cost ratio, along with total CO₂ emissions, and greenhouse gas intensity (GHGI). Across all years and regions, BRRI dhan98 consistently outperformed other varieties, recording the highest equivalent yield (4.40 to 5.56 t ha⁻¹) and economic return (Tk 4.46 to 5.80 × 10³ ha⁻¹), followed by BRRI dhan75 and BRRI dhan85. Environmental assessments revealed relatively stable total CO₂ emissions (7 to 9 × 10⁰ kg CO₂e) with moderate variations in GHGI, lowest for BRRI dhan98 (~5 kg CO₂ / 10 kg paddy) and highest for BRRI dhan82 and BRRI dhan48 (>6 kg CO₂ / 10 kg paddy). Overall, the findings indicate that DSR adoption, coupled with high-performing genotypes like BRRI dhan98 and BRRI dhan85, can enhance yield and profitability while maintaining moderate GHG intensity, particularly in Rangpur, where DSR adaptability and input efficiency are improving over time. These results highlight the potential of targeted varietal selection and site-specific management to optimize both economic returns and climate resilience in Bangladesh’s evolving rice systems.